Genetic Architecture and Anthocyanin Profiling of Aromatic Rice From Manipur Reveals Divergence of Chakhao Landraces - Bhuvaneswari, S.; Gopala Krishnan, S.; Bollinedi, Haritha; Saha, Supradip; Ellur, Ranjith Kumar; Vinod, K. K.; Singh, I. Meghachandra; Prakash, Narendra; Bhowmick, Prolay Kumar; Nagarajan, M.; Singh, Nagendra Kumar; Singh, Ashok Kumar (Frontiers in Genetics, 2020)
Aromatic rice of Manipur popularly known as Chakhao is a speciality glutinous rice, for which protection under geographical indication in India has been granted recently. The agronomic and nutraceutical variability of the Chakhao rice germplasm is yet to be genetically characterized. To address this gap, characterization of ninety-three landraces for agro-morphological traits, grain pigmentation, antioxidant properties, and molecular genetic variation was carried out to unravel their population genetic structure. Two major groups were identified based on pericarp color, namely, purple and non-purple, which showed a significant variation for plant height, panicle length, and grain yield. Molecular marker analysis revealed three subpopulations that could be associated with pericarp pigmentation. Deep purple genotypes formed POP3, japonica genotypes adapted to hill environment formed POP1, while POP2 comprised of both indica and aus types. Liquid chromatography–mass spectrometry (LC-MS) analysis revealed two major anthocyanin compounds in pigmented rices, namely, cyanidin-3-O-glucoside (C3G) and peonidin-3-O-glucoside (P3G). The total anthocyanin content among pigmented genotypes ranged from 29.8 to 275.8 mg.100g–1 DW. Total phenolics ranged from 66.5 to 700.3 mg GAE.100g–1 DW with radical scavenging activity (RSA) varying between 17.7 and 65.7%. Anthocyanins and phenolics showed a direct relationship with RSA implying the nutraceutical benefits of deep pigmented rice such as Manipur black rice. Aromatic rices from Manipur were found to be genetically diverse. Therefore, efforts need to be made for maintaining the geographic identity of these rice and utilization in breeding for region-specific cultivar improvement.